Psychoanalytic Perspectives on Psychopathology.
DOI: 10.1037/10138-003
|View full text |Cite
|
Sign up to set email alerts
|

Adult psychopathology associated with a history of childhood sexual abuse: A psychoanalytic perspective.

Abstract: Overview of the Researchn the late 1970s and 1980s, research interest in the sequelae of sexual I abuse mushroomed with the publication of dramatic clinical accounts describing the assessment and treatment of adult women who were abused as children (Butler, 1978; Herman, 1981). The demographics alone are striking: Estimates of the incidence of childhood sexual abuse range from 10% to 30% in the nonclinical adult female population (Briere

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Considering the moderate to high correlation between general psychopathology and psychological dissociation (Nash, Hulsey, Sexton, Harralson, & Lambert, 1993;Norton, Ross, & Novotny, 1990), some have expressed concern that dissociation scales may assess the former concept rather than the latter (Tillman, Nash, & Lerner, 1994). These authors could be correct, but this correlation could also reflect the broad comorbidity that characterizes complex dissociative disorders.…”
Section: Is Somatoform Dissociation a Unique Construct?mentioning
confidence: 99%
“…Considering the moderate to high correlation between general psychopathology and psychological dissociation (Nash, Hulsey, Sexton, Harralson, & Lambert, 1993;Norton, Ross, & Novotny, 1990), some have expressed concern that dissociation scales may assess the former concept rather than the latter (Tillman, Nash, & Lerner, 1994). These authors could be correct, but this correlation could also reflect the broad comorbidity that characterizes complex dissociative disorders.…”
Section: Is Somatoform Dissociation a Unique Construct?mentioning
confidence: 99%
“…History of childhood trauma has also been associated with greater dissociative symptoms in adulthood, including feelings of detachment, blunted emotional responsiveness, reduced awareness of surroundings, derealization, and depersonalization (e.g., Bosch et al, 2003; Briere, 2006; Briere et al, 1988; Chu et al, 1990; Dancu et al, 1996; Nash et al, 1993) Moreover, previous trauma history also predicted higher dissociative symptoms in soldiers early in military training and again later in response to intense training stressors (Morgan et al, 2007). Based on these findings, it has been suggested that dissociative symptoms develop as a trauma-related psychological reaction or alternatively, as a maladaptive way of coping with trauma-related distress.…”
mentioning
confidence: 99%
“…Despite the consistency of this statistical link and its general acceptance in clinical practice, some question still remains about the extent to which research has demonstrated that victimization actually causes symptoms. To date, research on the "effects" of child victimization has been conducted almost exclusively on cross-sectional studies of adult retrospective reports (e.g., Fromuth, 1986;Nash, Hulsey, Sexton, Harralson, & Lambert, 1993) or on children after they were victimized (e.g., Paradise et al, 1994). Although these studies have been Sue Boney-McCoy, Department of Psychology, Eastern Connecticut State University; David Finkelhor, Family Research Laboratory, University of New Hampshire.…”
mentioning
confidence: 99%
“…Consistent with this suggestion are data showing that adults and children who experienced child sexual abuse come from families with more impaired relationships than do nonabused individuals (e.g., Fromuth, 1986;Harteretal., 1988;Paradiseetal., 1994). In addition, poor family functioning has been associated with postvictimization symptomatology in several studies of sexual abuse (Harter et al, 1988;Nash et al, 1993;Paradise et al, 1994).…”
mentioning
confidence: 99%